Improving nutrition of underweight and stunting children through “DIGIDAU" innovation in Pesanggrahan District Health Centre - Atika Putri, Ika Agustin (Journal of Community Empowerment for Health, 2025)
Introduction: The World Health Organization Nutrition Guidelines recommend that exclusive breastfeeding can be given until 6 months, continuing breastfeeding until 2 years of age, and add complementary foods for their child. This Community Empowerment was held from May to July 2023 in Pesanggrahan District to reduce Stunting rates. Nutrition Diary in Overcoming Stunting (DIGIDAU) is an innovation to improve toddler nutrition by recording 24-hour food recalls every day for 5 weeks by mothers of toddlers. To aim the impact of "DIGIDAU" to reduce the incidence of malnutrition & stunting in children under five years by recording dietary patterns and improving parenting knowledge in Pesanggrahan.Method: A quantitative experimental research using a pre-experimental design study. One Group Pretest Posttest Design was used. The experimental group received treatment using the "DIGIDAU", where respondents' nutritional status was assessed before (pretest) and after (posttest) the treatment. The respondents for this research were 20 toddlers living in Pesanggrahan who met the research criteria. Data including toddlers’ weight and height and parents’ knowledge were collected and analyzed using paired sample t-tests.Results: Before the intervention, the respondents had poor knowledge around 17 mothers (85%). After the intervention, 20 mothers (100%) increased in knowledge. So that there was an impact of the counseling and training interventions on parents’ knowledge of parenting with P value =0.00 (< 0.05). Meanwhile, by recording dietary patterns & weight monitoring, there were 4 toddlers who experienced an increase in weight status according to age (Weight/age) from Underweight to Normal Weight. During the 5 weeks of the program, there was an increase in weight and height.Conclusion: The innovation of the Nutrition Diary in Overcoming Stunting “DIGIDAU” Program significantly increased the mother’s knowledge and the nutritional status of malnutrition and stunted toddlers.